TEENAGE PREGNANCY PREDICTION INDEX DURING THE ONLINE LEARNING PERIOD OF THE COVID-19 PANDEMIC - Qurniyawati, Eny; Martini, Santi; Syahrul, Fariani; Eka Sari, Jayanti Dian; Lubis, Rahayu; Gomaa Nasr, Nayla Mohamed (The Indonesian Journal of Public Health, 2024)
Introduction: The impact of the pandemic on adolescents' lives showed that 55.1% stress and 40% anxiety due to online learning along with an increase in teenage pregnancy. Aims: To determine the predictive index of risk variables for teen pregnancy throughout the COVID-19 pandemic's online learning period. Methods: This type of research is analytic observational utilizing a case-control design. Using simple random sampling, the case sample was 40 pregnant adolescents and 80 non-pregnant controls for the Indonesian Regency of Ngawi from July 2021 until January 2022. Once each variable was significant, multivariable logistic regression analysis was performed (p < 0.05) as predictors of teenage pregnancy. Results: The findings revealed that the variables as indicators of the risk of teenage pregnancy were courtship behavior, access to reproductive health media, and parenting. The predictive index of teen pregnancy risk factors was (-7.248 + 3.833 x low risk dating + 7.726 x severe risk dating + 2.773 x access 1 media + 2.773 x access 2/more media + 3.871 x authoritarian and permissive parenting). The high probability of teenage pregnancy with an opportunity value above 0.5 is in adolescents with dating behavior or parenting patterns that show the highest risk, namely high-risk dating behavior or adolescents with authoritarian and permissive parenting patterns. Conclusion: It is hoped that this index can be considered and used as a measuring tool in assisting in reproductive health programs, in screening adolescents so that it can be known early on that adolescents have an increased risk of pregnancy.